(untitled) (Research, Society and Development, 2022)
The characterization of urban solid waste is of great importance in the decision making of the management of a sanitary landfill, as it allows to obtain relevant information in the study and application of adequate and efficient management models, namely in terms of collection, transport, recovery and treatment of the waste produced. In this context, the present work aims to obtain representative data of MSW from the consortium landfill in the Alagoas agreste through its gravimetric composition. For this, the regionalization of the area of influence of the landfill was used, in which each separate region was selected municipalities that could present a representative sample of MSW in the locality. The separated residues were made using the quartering method for better homogenization. The results show that the gravimetric composition of the landfill MSW has the highest organic matter (47.24%), followed by rigid/flexible plastic (22.35%) and sanitary waste (11.06%). In smaller amounts, rubber (0.90%), leather (0.22%) and wood (0.20%). The percentages obtained in this study may allow landfill management and municipalities to plan intervention actions aimed at improving waste management in cities and increasing the useful life of the sanitary landfill.